Improving river health: insights into initiating collaboration in a transboundary river basin. Issue 1 (2nd January 2016) - Plummer, Ryan; Baird, Julia; Krievins, Katrina; Mitchell, Simon J.
ABSTRACT: River health is a concern worldwide. Governance of river basins is particularly complicated when they are large scale and cross jurisdictional boundaries. Past approaches to making decisions in transboundary basins are limited and attention is increasingly being focused on the potential of collaboration. This research investigates the initiation phase of a collaborative conservation project (WWF-Canada Freshwater Program, St. John River project) in the St. John River Basin of Canada. A social-ecological inventory technique and social network analysis are used to identify the actors in the transboundary basin and their activities, perceptions and connections to river health, relationship with other stakeholders, and actual engagement with a milestone event in the project. Insights gained from exploring the relationships between/among these variables highlight the complicated nature of initiating collaboration. A common understanding of river health and a strong structure of connected actors were encouraging signs that collaboration may flourish, while the assertion of power and context surrounding the initiative were found to mediate its possibility. The collaborative potential of conservation projects in large-scale transboundary river basins may be enhanced through such research and by actively applying these insights.